A cinepedagogia enquando «grande função do cinema». Discursos, modelos e experiências do cinema educativo em Portugal (1920‑1950): o caso do Porto - Duarte, Joana Isabel (CEM – Cultura, Espaço & Memória, 2020)
The present paper aims to analyse some of the discourses and experiences on educational cinema during the first half of the 20th century in Portugal. The cinepedagogia («cinepedagogy») – as it is named in historical sources – embodies pedagogic activities that benefit from moving images. The use of cinema for education is discoursed since the first decades of the cinematograph, however, it was from the 1920s onwards that the discussion on educational cinema truly developed, and it lasted vividly until the 1950s. Along with a historical contextualisation of this movement in Portugal, the city of Porto was defined as a case study, for instigating the association of cinema and education prematurely and successfully. This research takes advantage of sources that usually aren’t used in the analysis of this phenomenon in Portugal: specialized publications in cinema, such as magazines and newspapers. These sources demonstrate the discussion regarding educational cinema and publicise the concretizations in this field. Therefore, the review of the Portuguese cinematographic magazines, along with bibliographic resources, was fundamental for this study.